Эффективное алмазное шлифование неметаллических, труднообрабатываемых материалов усовершенствованным способом - Турманидзе, Р. С.; Буцхрикидзе, Д. С. (НТУ "ХПИ", 2012)
Problems connected with the workability of the scale of hard and brittle, intractable non-metallic materials during diamond grinding by the ring face by progressive method and influences of orientation of the sapphire mono-crystal on the output parameters of the process have been considered.
Keywords: обработка механическая; доводка; круг абразивный; зерно абразивное; сапфир